2017
DOI: 10.1111/ecaf.12218
|View full text |Cite
|
Sign up to set email alerts
|

Shifting from Undersupply to Oversupply: Does NHS Workforce Planning Need a Paradigm Shift?

Abstract: The National Health Service in England is currently halfway through the most austere decade in its history. Finding ways to improve health care efficiency is crucial to ensure the sustainability of the health system. While evidence of supply-induced demand (SID) has often been used as an economic argument to restrict labour supply, in the UK the risks of SID may be much less than in health care systems with more deregulated entry into the market post-qualification and with fee-for-service payment systems. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This report highlights the risks posed by growing NHS workforce shortages to the ability of the NHS to deliver pre-pandemic standards of care, calling for policy action and regular, longer term workforce planning. While there is relatively little evidence on how workforce undersupply affects health service delivery, 10 one recent study points to a direct link between registered nurse vacancy rates and patient safety in hospitals. 11 Workforce planning is also inextricably linked with NHS funding choices and pressures.…”
Section: Introduction 11 Contextmentioning
confidence: 99%
“…This report highlights the risks posed by growing NHS workforce shortages to the ability of the NHS to deliver pre-pandemic standards of care, calling for policy action and regular, longer term workforce planning. While there is relatively little evidence on how workforce undersupply affects health service delivery, 10 one recent study points to a direct link between registered nurse vacancy rates and patient safety in hospitals. 11 Workforce planning is also inextricably linked with NHS funding choices and pressures.…”
Section: Introduction 11 Contextmentioning
confidence: 99%
“…This adds to the often repeated challenge to governments and professional associations to ease and speed processes for recognition and integration of skilled overseas professionals. Countries like the UK have a shortage of skills in medicine (Charlesworth and Lafond, 2017) and education (Education Policy Unit, 2018) that could be mitigated by more flexible and efficient accreditation processes (Stewart, 2007). Furthermore, it highlights the difficulty even well-educated professionals face in finding career information.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses comprise 38 per cent of the health service staff. Charlesworth (2017) found that nurses in Ireland were the thirdhighest paid in the OECD after those in the US and Luxembourg, and were paid 38 per cent more than the OECD 29-country average.…”
Section: Rent-seeking Across the Irish Economymentioning
confidence: 98%